2014
DOI: 10.2174/1567205011666140812115818
|View full text |Cite
|
Sign up to set email alerts
|

Bone Loss and Osteoporosis are Associated with Conversion from Mild Cognitive Impairment to Alzheimer’s Disease

Abstract: Osteoporosis was associated with an increased risk of incident AD dementia. Additionally, low BMD at baseline was associated with an increased risk of AD in both women and men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 0 publications
3
40
1
1
Order By: Relevance
“…Osteoporosis and Alzheimer’s disease (AD) are common chronic degenerative disorders which are strongly associated with advanced age [1,2,3]. AD is frequently associated with fractures and reduction in bone mineral density, even at early stages of disease when patients are still active [4,5,6], indicating that AD and osteoporosis may share conserved pathogenic mechanisms. We have previously shown that there is a significant elevated expression levels of amyloid β peptide (Aβ), one of the pathological hallmarks of AD, in osteoporotic bone tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis and Alzheimer’s disease (AD) are common chronic degenerative disorders which are strongly associated with advanced age [1,2,3]. AD is frequently associated with fractures and reduction in bone mineral density, even at early stages of disease when patients are still active [4,5,6], indicating that AD and osteoporosis may share conserved pathogenic mechanisms. We have previously shown that there is a significant elevated expression levels of amyloid β peptide (Aβ), one of the pathological hallmarks of AD, in osteoporotic bone tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Low BMD and cognitive impairment share several common risk factors, and previous studies found an association of osteoporosis with stroke, brain atrophy, brain white matter changes, and silent infarcts [46]; also, it has been reported that low BMD and cognitive impairment often coexist, and that osteoporosis is associated with increased rates of progression from mild cognitive impairment to Alzheimer’s disease, as well as with incident Alzheimer disease [7, 8]. In addition, there is evidence of an increased risk of dementia in subjects with diagnosis of osteoporosis or osteoporotic fractures in Asian populations [1]; however, there are relevant racial differences in bone mass, so that Asian women have lower bone mass than Caucasian [9].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that lower BMD is associated with the higher risk of AD in Western population [44]. Zhou et al [45] also report that low BMD could predict the likelihood of progression to AD in patients with mild cognitive impairment. Although there are complicated associations between AD and BMD, we performed a MR analysis and found that there was no significant causal associations of AD with BMD.…”
Section: Discussionmentioning
confidence: 99%